The corner of Holly and Ivy - Mason, Debbie (Novelist) (Mason, Debbie (Novelist). Harmony Harbor novel., 2018)
With her dreams of being a wedding dress designer suddenly over, Arianna Bell isn't expecting a holly jolly Christmas. Instead, her heart feels about three sizes too small. That is until her high school sweetheart Connor Gallagher returns to town and she finds his mere presence still makes her pulse race. But just when she starts dreaming of kissing under the mistletoe, he announces that he will be her opponent in the upcoming mayoral race....Hot-shot attorney Connor Gallagher has something to prove. He's tired of playing runner-up to his high-achieving brothers. So when the opportunity to enter the campaign comes up, he takes it. Even if it means running against the only woman he's ever loved. But with a little help from Harmony Harbor's local matchmakers and a lot of holiday cheer, Connor and Arianna may just get the happy ever after they both deserve.